Sistem Informasi Penjualan Roti Rona Cake & Bakery Berbasis CMS - Agus Ridho Hidayat; Sri Widiyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Bread Sales Information System Based on CMS (Content Management System) “Rona Cake & Bakery” is a technological innovation that aims to improve operational efficiency and effectiveness in the bread and cake business “Rona Cake & Bakery”. In the increasingly advanced digital era, the use of information technology is crucial in achieving business success. This paper discusses in depth the development and implementation of a CMS-Based Sales Information System in the “Rona Cake & Bakery” business. This paper includes needs analysis, system design, implementation, and testing, as well as the expected benefits of using this system. The CMS-Based Sales Information System allows “Rona Cake & Bakery” to improve product sales management, expand customer reach, and improve the shopping experience for consumers. With this platform, customers can easily place orders online, choose the desired products, and make payments securely. The expected benefits of implementing this Sales Information System are increased operational efficiency, increased business competitiveness in the culinary industry, and increased customer satisfaction through better service